A novel intervention for post-treatment oxaliplatin chemotherapy-induced neuropathy. (1st April 2011) - Storey, D J; Colvin, L A; Boyle, D; Fallon, M T
Abstract : Abstract: Introduction/aims: Oxaliplatin chemotherapy-induced peripheral neuropathy (OxCIPN) is a common post-treatment toxicity. Many patients are left with long-term pain and disability. Available systemic agents have limited efficacy, cause significant side-effects and take several weeks/months to work. Colleagues' preclinical work showed analgesic effects of topical transient receptor potential melastatin receptor activators in neuropathic pain. We therefore conducted a proof-of-concept study using menthol in patients with OxCIPN. Methods: 21 patients a median of 19 months post-treatment (range 3–35) applied 1% topical menthol, twice daily to affected areas and skin overlying corresponding dorsal root ganglia. At baseline, 2 and 6 weeks, patients completed: Brief Pain Inventory (BPI), Hospital Anxiety and Depression Scale and underwent objective assessments of gait (electronic walkway), hand dexterity (peg-board) and Quantitative Sensory Testing. Analysis: Wilcoxon signed-rank test and Pearson product-moment correlation. Results: Between baseline and 6 weeks, total BPI scores decreased (median 3.6 (range 1.1–7.9) versus 0.7 (0–8.3), p=0.002). 83% described less pain and 52% had ≤30% BPI decrease (deemed clinically significant). There were corresponding improvements in mood (r=0.442, p=0.045), walking velocity (r=-0.797, p=0.026) and cadence (r=-0.823, p=0.012) and trends for improved hand dexterity (r=0.487, p=0.065) and mechanical pain thresholds (r=0.447, p=0.072). Four patients discontinued treatment after 2 weeks: two had difficulty applying the cream, two described worse pain. BPI changes were predicted by pre-treatment mechanical detection thresholds (r=0.534, p=0.027). Conclusion: Topical menthol appeared to improve OxCIPN pain and physical function. It also seems to be well tolerated, have minimal side-effects, works relatively quickly and warrants further study.